Efficacy of Povidone Iodine Against Microbial Biofilms in Breast Implants With Different Textures: Results From an in vitro Study - Fernández-Ibarburu, Borja; Díaz-Navarro, Marta; Ibarra, Gorka; Rivera, Andrés; Hafian, Rama; Irigoyen, Ãlvaro; Carrillo, Raquel; Pérez-Cano, Rosa; Muñoz, Patricia; García-Ruano, Ángela; Lasso, José M.; Guembe, María (Frontiers in Microbiology, 2022)
Background: In the practice of breast augmentation and reconstruction, implant irrigation with various solutions has been widely used to prevent infection and capsular contracture, but to date, there is no consensus on the optimal protocol to use. Recently, application of povidone iodine (PI) for 30 min has shown in vitro to be the most effective irrigating formula in reducing contamination in smooth breast implants. However, as 30 min is not feasible intraoperatively, it is necessary to determine whether shorter times could be equally effective as well as to test it in both smooth and textured implants. Methods: We tested the efficacy of 10% PI at 1', 3', and 5' against biofilms of 8 strains (2 ATCC and 6 clinical) of Staphylococcus spp. on silicone disks obtained from Mentor® and Polytech® implants of different textures. We analyzed the percentage reduction of cfu counts, cell viability and bacterial density between treatment (PI) and control (sterile saline, SS) groups for each time of application. Results: No bacteria were recovered from the culture of disks sonication at any of the 3 exposure times with PI treatment in textured implants. Considering clinical significance (>25% reduction of cell viability or bacterial density), none of the implants reached enough percentage reduction of living cells. Only 25 – 50 µm Polytxt® Polytech® implants showed best reduction of bacterial density at the three PI exposure times. Conclusion: PI applied at least during 1’ to the surface of breast implants is able to inhibit bacterial growth. However, no impact was demonstrated on living cells or bacterial density, which may be caused by differences in texture that directly affect PI absorption.